2017
DOI: 10.1021/acsami.7b06436
|View full text |Cite
|
Sign up to set email alerts
|

Double-Protected All-Inorganic Perovskite Nanocrystals by Crystalline Matrix and Silica for Triple-Modal Anti-Counterfeiting Codes

Abstract: Novel fluorescence with highly covert and reliable features is quite desirable to combat the sophisticated counterfeiters. Herein, we report a simultaneously triple-modal fluorescent characteristic of CsPbBr@CsPbBr/SiO by the excitation of thermal, ultraviolet (UV) and infrared (IR) light for the first time, which can be applied for the multiple modal anti-counterfeiting codes. The diphasic structure CsPbBr@CsPbBr nanocrystals (NCs) was synthesized via the typical reprecipitation method followed by uniformly e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
220
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 253 publications
(225 citation statements)
references
References 41 publications
2
220
0
3
Order By: Relevance
“…The results indicated that the intensities of PL emission were ever‐decreases with increasing the temperature. This is in accordance with the reported luminescent materials because the nonradiative transition was enhanced at a high temperature . The green emission of Cs 4 PbBr 6 was completely quenched at 175 °C (Figure a).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The results indicated that the intensities of PL emission were ever‐decreases with increasing the temperature. This is in accordance with the reported luminescent materials because the nonradiative transition was enhanced at a high temperature . The green emission of Cs 4 PbBr 6 was completely quenched at 175 °C (Figure a).…”
Section: Resultssupporting
confidence: 91%
“…To elucidate this, experiments were performed respectively using DMSO and toluene as a substitute for DMF. As shown in Figure S6, Cs 4 PbBr 6 perovskites solids with a bright green luminescence were readily produced if DMSO was used as DMF substitute because of their similar solubility for CsBr and PbBr 2 (Sample 2 in Figure S6) . Whereas, the yellow products composed of Cs 4 PbBr 6 , CsBr and PbBr 2 were obtained after 30 min by toluene, a poor solvent for CsBr and PbBr 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the emission colors under UV excitation were changed from brilliant yellow for uncoated QDs to dark yellow (100 µL), brilliant yellow (200 µL), and dark yellow (300 µL) (Figure S7, Supporting Information). This phenomenon can be explained that SiO 2 could restrain the activated nonradiative deactivation of Mn 2+ and exciton emissions in the CsPbX 3 QDs . The absolute PLQYs of 54.7%, 47.9%, 50.5%, and 33.5% for the pure CsPbMnX 3 , CsPbMnX 3 @SiO 2 (100 µL), CsPbMnX 3 @SiO 2 (200 µL), and CsPbMnX 3 @SiO 2 (300 µL), respectively, are obtained.…”
Section: Resultsmentioning
confidence: 88%
“…30 In addition, another LED based on silica encapsulation of the Cs 4 PbBr 6 -passsivated CsPbBr 3 NCs was also reported. 38 Moreover, several groups have used transmission electron microscopy (TEM) to identify the presence of green luminescent CsPbBr 3 NCs in Cs 4 PbBr 6 microcrystals, as well as in Cs 4 PbBr 6 NC solutions (Figure 2e). 30,31,34,62 …”
mentioning
confidence: 99%